Pré tratamento dentinário influência do condicionamento ácido, irradiação laser e hipermineralização na resistência ao cisalhamento de sistema adesivo multi uso - Gonçalves, Sérgio Eduardo de Paiva [UNESP] (Universidade Estadual Paulista (Unesp), 1997)
The disadvantages generated by the acid etching of the dentin, such as an increase in its permeability, in the surface moisture and in the potential to denature the external dentinal collagen, the formation of a fragility zone and the citotoxicity of the adhesive monomers; which are all aggravated by the depth of the dentin, have stimulated new and different treatment philosophies of the dentin. The purpose of the present study, therefore, was to investigate the effects of three dentin treatments: laser irradiation, acid etching and hypermineralization, in the shear bond strength of the SMP Plus bonding system. Sixty bovine incisors were extracted and randomly selected immediatly alter the animal's death. They were kept frozen (-18°C) for no longer than 14 days. After buccal dentinal surface had been exposed, X-Rays were taken to control the dentin thickness. The specimens were separated into two groups: (1) Control, kept in distilled water at 4ºC; (2) Mineralized, kept in hypermineralized solution at 4°C for 14 days. Each group was divided into three sub-groups according to the type of dentin treatment used: group F - followed the manufacturer instructions (acid-etching + primer + bond), group AL (acid-etching + primer + bond + laser) and group LA (laser + (laser + acid-etching + primer + bond). A composite resin standard cylinder (Z100-3M) was bond to the dentinal surface and the shear bond strength performed on a Universal lnstron machine 4301, with 500 Kg load and at 0,5mm/min. speed. The analysis of variance (ANOVA) determined that the treatments influenced the shear bond strength values (p<0,05) with the following average shearing load at failure: AL (9,96 MPa), F (7,28MPa) e LA (4,87 MPa). The interaction between the two factors analyzed Group (control and mineralized) and treatment (F, AL, LA) also influenced the shear bond strength (p<0,05). The highest values were obtained...

As desvantagens geradas pela técnica do condicionamento ácido total como o aumento da permeabilidade e umidade superficial, do potencial de denaturação do colágeno, a criação da zona de fragilidade e a citotoxicidade dos monômeros adesivos, sobretudo em função da profundidade, têm estimulado a pesquisa de novos tratamentos do substrato dentinário. Este trabalho tem como objetivo avaliar os efeitos do pré-tratamento da dentina com irradiação laser, condicionamento ácido e hipermineralização, na resistência de união do sistema adesivo SMUP, frente ao teste de cisalhamento. Foram empregados sessenta incisivos bovinos íntegros, imediatamente extraídos após o abate e conservados em freezer -18°C, por não mais de 14 dias. Após a exposição da superfície dentinária vestibular, radiografias foram tomadas pela técnica do cone longo, com a finalidade de controlar a espessura do remanescente dentinário. Os espécimens foram divididos em dois grupos: (1) Controle, imerso em água destilada e conservado em geladeira a 4°C até o descongelamento; (2) Mineralizado, imerso em solução hipermineralizante por 14 dias, em geladeira a 4°C. Cada grupo foi dividido em três sub-grupos, conforme o pré-tratamento da dentina: F - conforme o fabricante (condicionamento ácido + primer + adesivo); AL (condicionamento ácido + primer + adesivo + laser); LA (laser + condicionamento ácido + primer + adesivo). Um cilindro padronizado de resina composta (Z100-3M) foi confeccionado sobre a superfície dentinária e a resistência adesiva testada em máquina lnstron Universal 4301, com carga de 500 kg e uma velocidade de 0,5mm/min. O modelo estatístico de ANOVA, a um nível de significância de 5%, revelou que os Pré-Tratamentos influenciaram significativamente a resistência adesiva (p<0,05), proporcionando efeitos médios na ordem AL (9,96 MPa), F (7,28 MPa) e LA (4,87 MPa)....
Keywords: Dentina; Adesivos dentarios; Obturações (Odontologia); Lasers em odontologia; Dentin